2015
DOI: 10.1158/1940-6207.capr-14-0224
|View full text |Cite
|
Sign up to set email alerts
|

The Heat Shock Protein 90 Inhibitor, (−)-Epigallocatechin Gallate, Has Anticancer Activity in a Novel Human Prostate Cancer Progression Model

Abstract: (−)-Epigallocatechin gallate (EGCG), a major tea polyphenol, elicits anti-cancer effects. However, the mechanism of action is not fully understood. Our laboratory previously showed that EGCG inhibits heat shock protein 90 (HSP90). We utilized non-tumorigenic (NT), tumorigenic, and metastatic cancer cells from a novel human prostate cancer (PRCA) progression model to test the hypotheses that certain stages are more or less sensitive to EGCG and that sensitivity is related to HSP90 inhibition. Treatment of cells… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 35 publications
1
31
0
Order By: Relevance
“…Hsp90 is commonly overexpressed in cancer cells and stabilizes many clients known to promote oncogenesis, including transcription factors, signaling proteins and kinases [9,16]. Multiple studies have shown that certain tumor cells are more dependent on Hsp90 activity compared to non-malignant cells [1719].…”
Section: Introductionmentioning
confidence: 99%
“…Hsp90 is commonly overexpressed in cancer cells and stabilizes many clients known to promote oncogenesis, including transcription factors, signaling proteins and kinases [9,16]. Multiple studies have shown that certain tumor cells are more dependent on Hsp90 activity compared to non-malignant cells [1719].…”
Section: Introductionmentioning
confidence: 99%
“…HSP90 also participates in regulation of gene expression and genome maintenance (Fang et al 2014); (Sollars et al 2003;Lu et al 2012a, b). Despite these uncertainties, the observation that H90Ins as a class concentrate in tumor cells to a greater degree than in normal tissue is of importance and a point of hope (Kamal et al 2003); (Moulick et al 2011); (Taldone et al 2014); (Suzuki et al 2015); (Moses et al 2015). The notion that rapidly proliferating malignant cells in a toxic microenvironment have a larger population of targetable molecular chaperones such as HSP90, and depend more on these proteostasis components for survival, fits well with the concept of chaperone addiction put forth by many others in the field (Miyata et al 2013); (Prodromou 2009); (Workman et al 2007a); (Calderwood et al 2006); (Xiao et al 2007); ( Barrott and Haystead 2013).…”
Section: Resultsmentioning
confidence: 99%
“…EGCG, with Hsp90 inhibition, showed a protective effect against cancer in a novel human prostate cancer progression model [58]. In primary vascular endothelial cells, GST and NQO1 enzymes were increased dose-dependently by Nrf2 [59].…”
Section: Epigallocatechin Gallatementioning
confidence: 95%